PENGARUH PERSEPSI DUKUNGAN ORGANISASI DAN LINGKUNGAN KERJA TERHADAP PERILAKU KEWARGAAN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI INTERVENING - Marwah An Aisyah Hasanah Nur; Prayekti Prayekti; Didik Subiyanto (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the influence of organizational support perception and work environment on organizational citizenship behavior with job satisfaction as an intervening variabel in the Pamong Praja Police Unit of Yogyakarta City.The type of research used in this research is descriptive quantitative research. The result Perception organizational support has a significant positive effect on job satisfaction, work environment has a significant positive effect on job satisfaction, job satisfaction has a significant positive effect on organizational citizenship behavior, Perception organizational support has a significant positive effect on organizational citizenship behavior, Work environment does not have a positive and significant effect on organizational citizenship behavior, Perception organizational support has a positive and significant effect on organizational citizenship behavior with job satisfaction as an intervening variable , and Work environment has a positive and significant effect on organizational citizenship behavior with job satisfaction as an intervening variable. Keyword: Perception Organizatioinal Support, Work Environment, OCB, and Job Satisfaction.